Zlatý expres Príbeh Antona Tkáča - Bakalář, Robert; Husárová, Viola; Pospíšil, Peter; Meisner, Jan; Drhlík, Jan; Pekárek, Jiří; Pospíšil, Peter; Puklický, Luboš; Richter, Dalibor; Skála, Jaroslav (Bratislava Šport, 1980)
Príbeh Antona Tkáča
Fot. na front.
Keywords: životopis; Anton Tkáč; Biografie a memoáre